Cache Coherence Protocol Design and Simulation Using IES (Invalid Exclusive read/write Shared) State (Baghdad Science Journal, 2017)
To improve the efficiency of a processor in recent multiprocessor systems to deal with data, cache memories are used to access data instead of main memory which reduces the latency of delay time. In such systems, when installing different caches in different processors in shared memory architecture, the difficulties appear when there is a need to maintain consistency between the cache memories of different processors. So, cache coherency protocol is very important in such kinds of system. MSI, MESI, MOSI, MOESI, etc. are the famous protocols to solve cache coherency problem. We have proposed in this research integrating two states of MESI's cache coherence protocol which are Exclusive and Modified, which responds to a request from reading and writing at the same time and that are exclusive to these requests. Also back to the main memory from one of the other processor that has a modified state is removed in using a proposed protocol when it is invalidated as a result of writing to that location that has the same address because in all cases it depends on the latest value written and if back to memory is used to protect data from loss; preprocessing steps to IES protocol is used to maintain and saving data in main memory when it evict from the cache. All of this leads to increased processor efficiency by reducing access to main memory